Relationships between Learning and Motivation Strategies in Vocational Technical Education - Satico Ferraz, Adriana (2022)
This research’s main objective was to investigate the evidence of validity based on the relationship with other variables of the Learning Strategies Assessment Scale for Vocational Education. The sample study was 401 Brazilian students. Learning strategies were associated with achievement goals at a correlational and predictive level. The secondary objective was to analyze the differences in both constructs regarding age, pause in studies, and the number of modules taken. Older students differed from younger students in the absence of dysfunctional metacognitive strategies and cognitive strategies. We identified the performance-approach goal in the younger students and those who took an intermediate break from studies. We recommend further research on this topic.